Hijacking the rule of law in postconflict environments. (17th September 2018) - Sesay, Mohamed
Abstract: The positive effects of rule of law norms and institutions are often assumed in the peacebuilding literature, with empirical work focusing more on processes of compliance with international standards in war-torn countries. Yet, this article contends that purportedly 'good' rule of law norms do not always deliver benign benefits but rather often have negative consequences that harm the very local constituents that peacebuilders promise to help. Specifically, the article argues that rule of law promotion in war-torn countries disproportionately favours actors who have been historically privileged by unequal socio-legal and economic structures at the expense of those whom peacebuilders claim to emancipate. By entrenching an inequitable state system which benefits those with wealth, education, and influence, rule of law institutions have reinforced structural, social, and cost-related barriers to justice. These negative effects explain why war-torn societies avoid the formal courts and law enforcement agencies despite substantial international efforts to professionalise and strengthen these institutions to meet global rule of law standards. The argument is drawn from an historical, comparative, and empirical analysis of the UK-funded justice sector development programme in Sierra Leone and US-supported rule of law reforms in Liberia – two postwar countries often cited as prototypes of successful peacebuilding.